2021
DOI: 10.1063/5.0057475
|View full text |Cite
|
Sign up to set email alerts
|

A large-eddy simulation study on vortex-ring collisions upon round cylinders

Abstract: A large-eddy simulation study on vortex-ring collisions upon round cylinders. Physics of Fluids, 33(9), 094101-.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
3
12
0
Order By: Relevance
“…On the other hand, the collision behaviour along the cylinder straight edges is more reminiscent of vortex ring collisions with flat walls, with vortex stretching effects leading to increasingly smaller vortex structures accompanying reductions in the cylinder diameter ratio. In the follow-up large-eddy simulations (LES) study by New et al (2021), simulation results showed good agreement with the vortex flow models proposed in the earlier study, and revealed further that the vortex ringlets undergo axis-switching like elliptic vortex rings. In addition, vortex core trajectories along the convex surface plane extracted from the numerical results also agree well with the experimental results, on top of allowing more accurate trajectory extraction of the vortex cores along the cylinder straight edges.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, the collision behaviour along the cylinder straight edges is more reminiscent of vortex ring collisions with flat walls, with vortex stretching effects leading to increasingly smaller vortex structures accompanying reductions in the cylinder diameter ratio. In the follow-up large-eddy simulations (LES) study by New et al (2021), simulation results showed good agreement with the vortex flow models proposed in the earlier study, and revealed further that the vortex ringlets undergo axis-switching like elliptic vortex rings. In addition, vortex core trajectories along the convex surface plane extracted from the numerical results also agree well with the experimental results, on top of allowing more accurate trajectory extraction of the vortex cores along the cylinder straight edges.…”
Section: Introductionsupporting
confidence: 79%
“…2007; Cheng, Lou & Luo 2010; Couch & Krueger 2011; New, Shi & Zang 2016; Xu & Wang 2016; Mishra, Pumir & Ostilla-Mónico 2021), porous walls (Adhikari & Lim 2009; Hrynuk, Van Luipen & Bohl 2012; Naaktgeboren, Krueger & Lage 2012; Cheng, Lou & Lim 2014; Xu et al. 2018), and concave or convex surfaces (New & Zang 2017; New, Gotama & Vevek 2021; Chen, Gao & Chen 2022; Ahmed & Erath 2023), and under confined conditions (Stewart et al. 2012; Danaila, Kaplanski & Sazhin 2017; Zhang & Rival 2020; Hu & Peterson 2021), among others, with the primary interest surrounding how the vortex dynamics unfolds during the collisions and how it differs when the scenario varies.…”
Section: Introductionmentioning
confidence: 99%
“…While the dynamic Smagorinsky model (Germano et al 1991;Lilly 1992), with the Smagorinsky constant computed in terms of the local flow conditions, is often used for jet flows, the classical Smagorinsky model has been shown to produce comparable accuracy in a number of recent investigations of vortex ring related flows at a similar Re (e.g. New, Gotama & Vevek 2021). As to the discretisation specifics, PISO (pressure-implicit with splitting of operators) is employed in the pressure velocity coupling algorithm (Issa 1986); a second-order difference scheme was implemented for all the spatial derivative terms, and the time step set at 1 × 10 −4 ensuring a maximum Courant-Friedrichs-Lewy (CFL) number below 1 for all the flow cases explored.…”
Section: Mesh Decomposition Methods Of Solution and Validationmentioning
confidence: 99%
“…Structured grid used in this study. The accuracy of different turbulence models was verified, including the Laminar model, 31 RSM model, and LES model 32–36 . The corresponding y+$$ {y}^{+} $$ values were selected for different turbulence models.…”
Section: Methodsmentioning
confidence: 99%
“…The accuracy of different turbulence models was verified, including the Laminar model, 31 RSM model, and LES model. [32][33][34][35][36] The corresponding y + values were selected for different turbulence models. For the RSM model, the high Reynolds number turbulence model requires higher y + value (30 < y + <500).…”
Section: Computational Domain and Meshmentioning
confidence: 99%